The Characteristics of Fandom Reveluv as A Cyberfandom of Red Velvet on Twitter - Edi Dwi Riyanto (Unipdu Jombang, 2021)
The existence of social media, including Twitter, supports the popularity of K-Pop music in Indonesia. The fan enjoyment practice in digital media, called cyberfandom, has unique characteristics that indicate the latest trend of fandom in Indonesia. The study of cyberfandom trends can be used as a reference for the digital generation to develop their creativity and potential in accordance with their fields and times. This current study aims to review the characteristics of cyberfandom practices carried out by the fans of K-Pop music on social media. To do this, the descriptive qualitative approach is applied. The object of the research is Red Velvet, one of the popular girl bands from Korea. The data were collected through participant observation of Red Velvet's Twitter fandom followers. The result shows that there were various socialization activities on cyberfandom. The fans did not only enjoy the works of their favorite groups but also produced fan arts and traded photocards and various fansite knick-knacks. The existence of production activities in addition to consumption activities shows that the cyberfandom of Korean music-lovers had become a prosumer. The presence of a digital platform had perpetuated the commodification of fandom in Indonesia.